The Influence of Organizational Commitment on the Performance of Nias Regency Food Security Agriculture and Fisheries Service Employees - Halawa, Oliziduhu; Sadalia, Isfenti; Meliala, Janita S. (International Conference on Sciences Development and Technology, 2022)
This research aims to investigate the influence of organizational commitment on the performance of employees of the Nias Regency Food Security, Agriculture and Fisheries Service. Organizational commitment is a key factor in understanding the level of employee engagement and productivity in a government organization. This study involved employees of the Nias Regency Food Security, Agriculture, and Fisheries Service as respondents.This research uses a survey method by distributing questionnaires to randomly selected respondents. This questionnaire includes questions about the level of organizational commitment and employee performance. The collected data is then analyzed using appropriate statistical methods.The results of this research show that there is a significant positive influence between organizational commitment and the performance of employees of the Nias Regency Food Security, Agriculture, and Fisheries Service. This means that the higher the level of organizational commitment that employees have, the better their performance in carrying out their duties.This research has important implications for the management of the Nias Regency Food Security, Agriculture, and Fisheries Service in improving the performance of their employees. By strengthening organizational commitment, they can motivate employees to work more effectively and efficiently in carrying out food security, agriculture, and fisheries tasks.